Genomic Snapshot of SARS-CoV-2 in Migrants Entering Through Mediterranean Sea Routes - Grandi, Nicole; Paglietti, Bianca; Cusano, Roberto; Ibba, Gabriele; Lai, Vincenzo; Piu, Claudia; Angioj, Flavia; Serra, Caterina; Kelvin, David J.; Tramontano, Enzo; Rubino, Salvatore (Frontiers in Public Health, 2022)
In December 2019, a novel coronavirus emerged in Wuhan, China, rapidly spreading into a global pandemic. Italy was the first European country to experience SARS-CoV-2 epidemic, and one of the most severely affected during the first wave of diffusion. In contrast to the general restriction of people movements in Europe, the number of migrants arriving at Italian borders via the Mediterranean Sea route in the summer of 2020 had increased dramatically, representing a possible, uncontrolled source for the introduction of novel SARS-CoV-2 variants. Importantly, most of the migrants came from African countries showing limited SARS-CoV-2 epidemiological surveillance. In this study, we characterized the SARS-CoV-2 genome isolated from an asymptomatic migrant arrived in Sardinia via the Mediterranean route in September 2020, in comparison with SARS-CoV-2 strains arrived in Sicily through the Libyan migration route; with SARS-CoV-2 isolates circulating in Sardinia during 2020; and with viral genomes reported in African countries during the same summer. Results showed that our sequence is not phylogenetically related to isolates from migrants arriving in Sicily, nor to isolates circulating in Sardinia territory, having greater similarity to SARS-CoV-2 genomes reported in countries known for being sites of migrant embarkation to Italy. This is in line with the hypothesis that most SARS-CoV-2 infections among migrants have been acquired prior to embarking to Italy, possibly during the travel to or the stay in crowded Libyan immigrant camps. Overall, these observations underline the importance of dedicated SARS-CoV-2 surveillance of migrants arriving in Italy and in Europe through the Mediterranean routes.